Futebol feminino: sua história e a busca pela igualdade - Vedove, Rebeca Dalle [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Since its emergence, women's football has suffered a lot of prejudice from a macho society that had dominated both the practice and the public who appreciate the sport. In Brazil it was no different, where women had to fight historically to get their role and the acceptance of society and governors to make the practice of sport legal and with the same resources that men’s football had. After many years since its first appearance, women's football still suffers from the prejudice of women in the practice, with the macho exposure in the media and with a salary inequality compared to male football athletes. The history and unwinding of this struggle for the equality of athletes within the sport and as professionals will be included in the present work

O futebol feminino desde seu surgimento sofreu muito com o preconceito e com a sociedade machista que dominava tanto a prática como o público apreciador do esporte. No Brasil não foi diferente, onde as mulheres tiveram que batalhar historicamente para conseguir seu papel e a aceitação da sociedade e dos governadores para tornar a prática do esporte legal e com os mesmos recursos que o futebol masculino possuía. Depois de muitos anos desde sua primeira aparição, o futebol feminino ainda sofre com o preconceito da mulher na prática, com a exposição machista na mídia e com a desigualdade salarial comparada com os atletas do futebol masculino. A história e os desdobramentos dessa luta pela igualdade das atletas dentro do esporte e como profissionais serão abordados no presente trabalho.
Women's football: your history and the quest for equality
Keywords: Women's football history; Prejudice in women's football; Salary inequality in women's football; Women's football exposure in the media; História do futebol feminino; Preconceito no futebol feminino; Desigualdade salarial no futebol feminino; Exposição do futebol feminino na mídia